Arabidopsis HEAT SHOCK TRANSCRIPTION FACTORA1b overexpression enhances water productivity, resistance to drought, and infection - Bechtold, Ulrike (Oxford University Press, 2013)
Heat-stressed crops suffer dehydration, depressed growth, and a consequent decline in water productivity, which is the yield of harvestable product as a function of lifetime water consumption and is a trait associated with plant growth and development. Heat shock transcription factor (HSF) genes have been implicated not only in thermotolerance but also in plant growth and development, and therefore could influence water productivity. Here it is demonstrated that Arabidopsis thaliana plants with increased HSFA1b expression showed increased water productivity and harvest index under water-replete and water-limiting conditions. In non-stressed HSFA1b-overexpressing (HSFA1bOx) plants, 509 genes showed altered expression, and these genes were not over-represented for development-associated genes but were for response to biotic stress. This confirmed an additional role for HSFA1b in maintaining basal disease resistance, which was stress hormone independent but involved H(2)O(2) signalling. Fifty-five of the 509 genes harbour a variant of the heat shock element (HSE) in their promoters, here named HSE1b. Chromatin immunoprecipitation-PCR confirmed binding of HSFA1b to HSE1b in vivo, including in seven transcription factor genes. One of these is MULTIPROTEIN BRIDGING FACTOR1c (MBF1c). Plants overexpressing MBF1c showed enhanced basal resistance but not water productivity, thus partially phenocopying HSFA1bOx plants. A comparison of genes responsive to HSFA1b and MBF1c overexpression revealed a common group, none of which harbours a HSE1b motif. From this example, it is suggested that HSFA1b directly regulates 55 HSE1b-containing genes, which control the remaining 454 genes, collectively accounting for the stress defence and developmental phenotypes of HSFA1bOx.